Analysis of Differentiated Learning Implementation Using a 3D Chemistry Periodic Table Application to Improve Students' Cognitive Ability - Natasya S. Safitri; Yenni Kurniawati (Universitas Tadulako, 2025)
The cognitive ability of each student is different. To improve it, it needs to be trained and optimized. The purpose of cognitive skills is the implementation of differentiated learning using a 3D Chemistry Periodic Table Application to improve the students’ cognitive ability. This research was implemented in the even semester academic year 2023 / 2024 at State Senior High School 1 Tambang. The method used in this research was mixed-method research with a research design Sequential Explanatory model, with research samples consisting of three classes of Grade X at State Senior High School 1 Tambang, namely two (2) experimental classes and one (1) control class. The post-test research result showed a significance of 0.000 < 0.05 until indicating a significant difference between the experimental and control classes. Besides, the average N-Gain of the experimental class namely 0.77, and the second experimental class was 0.71, with high category, and the control class was 0.60, with medium category. In other words, it is proven that differentiated learning with a 3D application increases cognitive ability. The students’ response after gaining the learning by using 3D was excellent, with a percentage of 81.41 %. The results of this research are expected to help teachers improve the students’ cognitive abilities.